Paleoaltimetry and paleotectonic reconstruction using triple oxygen and hydrogen isotopes: Depleted δ18O and δD values in ignimbrites of Verkhneavachinskaya caldera record collisional uplift during Miocene arc accretion to Kamchatka - Vialichka K.; Bindeman I.N.; Bergal-Kuvikas Olga; Rogozin Aleksei (My University, 2024)
Here we use δ18O and δD values as tools to investigate the paleo-altitude and the origin of large-volume (120 km3, 10 × 12 km) ignimbrites of Verkhneavachinskaya caldera (cf. Verkhne-Avachinskaya) (VC) in eastern Kamchatka, formed the in Late Miocene 5.8 Ma. The basaltic-andesitic intracaldera ignimbrite deposit exhibits low δ18O values, reaching −5.03‰, and δD values of −182‰ across a 1.2 km depth range in several sampled sections. The results support a massive meteoric-hydrothermal system throughout the cooling history of the thick intracaldera ignimbrite deposit. Using triple oxygen isotope data we estimate that the δ18O values of altering meteoric water are as low as −19‰ to −23‰, much lower than modern precipitation of −14‰, or − 16‰ estimated for the 2–3 °C warmer Kamchatka climate of the late Miocene. Therefore, the VC meteoric-hydrothermal system depended on high-altitude precipitation and glaciers, and altitudinal isotopic lapse rates suggest a paleo-altitude of 3.5 km at 5.8 Ma during caldera formation. These elevations exceed the modern by 1.5 km and provide a unique snapshot into an evolving landscape and paleo-environment of eastern Kamchatka at 6–5 Ma as the dynamic outcomes of accretion of the Kronotski arc. In particular, the existence of such a high plateau is in line with contemporary accretionary tectonics: accretion of the Shipunsky peninsula of this accreting arc terrain, ∼120 km to the east of the VC, and evidence of contemporaneous exhumation of high-grade Ganal amphibolites to the west. We conclude that the eruption of large-volume mafic ignimbrites that formed VC caldera was syncollisional or intracollisional in nature, likely requiring delamination of thickened crust to account for both uplift and magmatism.
Keywords: 38.17.21 Палеотектонические реконструкции; Кайнозой::Неоген::Миоцен; Cenozoic::Neogene::Miocene